Identifying personality dimensions in working African giant pouched rats using caregiver ratings - Vikki Neville; Pendo Msegu; J. Eduardo Reynoso-Cruz; Cynthia D. Fast (Applied Animal Behaviour Science, 2026)

Investigation of a novel assay for the proteomic screening of the secretory and excretory products of individual salmon lice Lepeophtheirus salmonis - Alexander Dindial; James E. Bron; Michael McGowan; Ava Drake; Kevin McLean; Dorota Androscuk; William Roy; Andre Van; Diego Robledo; Richard Paley; Claire Joiner; Mark D. Fast; et al. (Veterinary Parasitology, 2026)

Addressing risks to bioretention performance: The potential for pollutant leaching and groundwater interactions to overshadow design features - R. Andrew Tirpak; Claire Weldon; Jay D. Dorsey; Kathleen M. Fast; Haley Jenkins; Jennifer Grieser; Ryan J. Winston (Ecological Engineering, 2026)

Local inflammation at the salmon louse (Lepeophtheirus salmonis) attachment site contributes to copepodid rejection in coho salmon (Oncorhynchus kisutch) - Lene Sveen; Mark D. Fast; Torstein Tengs; Rachel A. Kline; Judit Aguilar Marti; Dominic Kurian; Gerrit Timmerhaus; Marianne Vaadal; Ross D. Houston; James E. Bron; Sean J. Monaghan; Haitham H. Mohammed; et al. (Cell and Tissue Research, 2025)
The study investigates the susceptibility of Atlantic salmon ( Salmo salar ) and Pacific salmon species (pink salmon, Oncorhynchus gorbuscha ; coho salmon, Oncorhynchus kisutch ; and chum salmon, Oncorhynchus keta ) to the parasitic salmon lice ( Lepeophtheirus salmonis ). The research had two main objectives: to characterize the morphology of the scaly skin in four salmonid species and to compare the cellular response at the louse attachment site in coho salmon and Atlantic salmon. Three consecutive challenge trials were conducted, with successful louse infestation only achieved across all four species in the third trial using mild anesthesia with tricaine methanesulfonate. Skin and fin samples were collected at 12, 24, 36, 48, 60, and 168 h post-infestation (hpi) for histological, proteomic, and spatial transcriptomic analyses. Results showed that chum salmon had significantly higher mucous cell coverage (30–40%) in the epithelium of scaly skin compared to Atlantic salmon (10%). At the louse attachment site in coho salmon, there was a greater influx of inflammatory cells at 36–48 hpi compared to Atlantic salmon. Proteomic analysis at 12 hpi and 36 hpi in coho salmon showed upregulation of neutrophil degranulation and formyl-methionyl-leucyl-phenylalanine signaling. Additionally, spatial transcriptomics at the attachment site showed local upregulation of inflammatory gene markers. These findings suggest that coho salmon mount a rapid and large-scale inflammatory response driven by neutrophils to louse attachment within the first 48 hpi. Overall, the study emphasizes the significance of local changes at the host-parasite interface for resistance mechanisms against salmon lice.

Polyrate 2023: A computer program for the calculation of chemical reaction rates for polyatomics. New version announcement - Rubén Meana-Pañeda; Jingjing Zheng; Junwei Lucas Bao; Shuxia Zhang; Benjamin J. Lynch; José C. Corchado; Yao-Yuan Chuang; Patton L. Fast; Wei-Ping Hu; Yi-Ping Liu; Gillian C. Lynch; Kiet A. Nguyen; et al. (Computer Physics Communications, 2024)

Applying genetic technologies to combat infectious diseases in aquaculture - Nicholas A. Robinson; Diego Robledo; Lene Sveen; Rose Ruiz Daniels; Aleksei Krasnov; Andrew Coates; Ye Hwa Jin; Luke T. Barrett; Marie Lillehammer; Anne H. Kettunen; Ben L. Phillips; Tim Dempster; et al. (Reviews in Aquaculture, 2023)
Disease and parasitism cause major welfare, environmental and economic concerns for global aquaculture. In this review, we examine the status and potential of technologies that exploit genetic variation in host resistance to tackle this problem. We argue that there is an urgent need to improve understanding of the genetic mechanisms involved, leading to the development of tools that can be applied to boost host resistance and reduce the disease burden. We draw on two pressing global disease problems as case studies—sea lice infestations in salmonids and white spot syndrome in shrimp. We review how the latest genetic technologies can be capitalised upon to determine the mechanisms underlying inter‐ and intra‐species variation in pathogen/parasite resistance, and how the derived knowledge could be applied to boost disease resistance using selective breeding, gene editing and/or with targeted feed treatments and vaccines. Gene editing brings novel opportunities, but also implementation and dissemination challenges, and necessitates new protocols to integrate the technology into aquaculture breeding programmes. There is also an ongoing need to minimise risks of disease agents evolving to overcome genetic improvements to host resistance, and insights from epidemiological and evolutionary models of pathogen infestation in wild and cultured host populations are explored. Ethical issues around the different approaches for achieving genetic resistance are discussed. Application of genetic technologies and approaches has potential to improve fundamental knowledge of mechanisms affecting genetic resistance and provide effective pathways for implementation that could lead to more resistant aquaculture stocks, transforming global aquaculture.

Impact of co‐infection with Lepeophtheirus salmonis and Moritella viscosa on inflammatory and immune responses of Atlantic salmon ( Salmo salar ) - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)
This study was conducted to determine the effects of a co‐infection with Moritella viscosa at different exposure levels of sea lice Lepeophtheirus salmonis in Atlantic salmon ( Salmo salar ). M. viscosa (1.14 × 10 6 cfu/ml) was introduced to all experimental tanks at 10 days post‐lice infection (dpLs). Mean lice counts decreased over time in both the medium lice co‐infection (31.5 ± 19.0 at 7 dpLs; 16.9 ± 9.3 at 46 dpLs) and high lice co‐infection (62.0 ± 10.8 at 7 dpLs; 37.6 ± 11.3 at 46 dpLs). There were significantly higher mortalities and more severe skin lesions in the high lice co‐infected group compared to medium lice co‐infected group or M. viscosa ‐only infection. Quantitative gene expression analysis detected a significant upregulation of genes in skin from the high lice co‐infection group consistent with severe inflammation ( il‐8 , mmp‐9 , hep, saa ). Skin lesions retrieved throughout the study were positive for M. viscosa growth, but these were rarely located in regions associated with lice. These results suggest that while M. viscosa infection itself may induce skin lesion development in salmon, co‐infection with high numbers of lice can enhance this impact and significantly reduce the ability of these lesions to resolve, resulting in increased mortality.

Cover Image - Laura A. Carvalho; Shona K. Whyte; Laura M. Braden; Sara L. Purcell; Anthony J. Manning; Anne Muckle; Mark D. Fast (Journal of Fish Diseases, 2020)

Genomic and phenotypic effects of inbreeding across two different hatchery management regimes in Chinook salmon - Charles D. Waters; Jeffrey J. Hard; David E. Fast; Curtis M. Knudsen; William J. Bosch; Kerry A. Naish (Molecular Ecology, 2020)
Genomic approaches permit direct estimation of inbreeding and its effect on fitness. We used genomic‐based estimates of inbreeding to investigate their relationship with eight adult traits in a captive‐reared Pacific salmonid that is released into the wild. Estimates were also used to determine whether alternative broodstock management approaches reduced risks of inbreeding. Specifically, 1,100 unlinked restriction‐site associated (RAD) loci were used to compare pairwise relatedness, derived from a relationship matrix, and individual inbreeding, estimated by comparing observed and expected homozygosity, across four generations in two hatchery lines of Chinook salmon that were derived from the same source. The lines are managed as “integrated” with the founding wild stock, with ongoing gene flow, and as “segregated” with no gene flow. While relatedness and inbreeding increased in the first generation of both lines, possibly due to population subdivision caused by hatchery initiation, the integrated line had significantly lower levels in some subsequent generations (relatedness: F 2 –F 4 ; inbreeding F 2 ). Generally, inbreeding was similar between the lines despite large differences in effective numbers of breeders. Inbreeding did not affect fecundity, reproductive effort, return timing, fork length, weight, condition factor, and daily growth coefficient. However, it delayed spawn timing by 1.75 days per one standard deviation increase in F (~0.16). The results indicate that integrated management may reduce inbreeding but also suggest that it is relatively low in a small, segregated hatchery population that maximized number of breeders. Our findings demonstrate the utility of genomics to monitor inbreeding under alternative management strategies in captive breeding programs.

Pathologic features of mycobacteriosis in naturally infected Syngnathidae and novel transcriptome assembly in association with disease - S B Fogelson; M D Fast; J Leary; A C Camus (Journal of Fish Diseases, 2017)
Syngnathidae (seahorses, seadragons and pipefish) suffer significant losses from non‐tuberculous mycobacteria. However, they produce markedly different lesions in response to the disease compared to other teleost species, notably infrequent granuloma formation. This study evaluated 270 syngnathid fish, from which 92 were diagnosed with mycobacteriosis by histopathology, culture or both. Microscopic lesions variably consisted of random foci of coagulative necrosis in multiple organs, containing high numbers of free bacteria and large aggregates or sheets of macrophages with cytoplasm laden with acid‐fast bacilli. Mycobacterial associated granulomas were identified in only six seahorses. Five fish had positive cultures with no observed microscopic changes. RNA ‐seq of the head kidney was performed to investigate the transcriptome of two infected and six non‐infected lined seahorses Hippocampus erectus . Assembled and annotated putative transcripts serve to enrich the database for this species, as well as provide baseline data for understanding the pathogenesis of mycobacteriosis in seahorses. Putative components of the innate immune system ( IL ‐1β, IL ‐6, TNF , NOS , Toll‐like receptor 1, MHC Class I, NF ‐κβ, transforming growth factor beta, MyD88) were identified in the RNA ‐seq data set. However, a homolog for a key component in the TH 1 adaptive immune response, interferon‐gamma, was not identified and may underlie the unique pathologic presentation.

Measures of immune system status in young‐of‐the‐year winter flounder Pseudopleuronectes americanus - J. S. Romany; A. E. McElroy; M. D. Fast (Journal of Fish Biology, 2015)
The immune status of young‐of‐the‐year ( YOY ) winter flounder Pseudopleuronectes americanus was evaluated in fish collected from six areas around Long Island, NY, U.S.A. representing more urban areas with high population density in the west, to less densely populated more rural areas in to the east. Gene expression markers for innate immunity ( pleurocidin ) and contaminant exposure (cytochrome P4501A ; cyp1a ) were measured in liver and fin of fish collected at each site. Expression of pleurocidin was significantly higher in fin than liver, but was highly variable among individuals. Some statistically significant differences in pleurocidin expression among sites were observed, although elevated levels were not associated with degree of urbanization. Expression was related in part to fish size: a positive correlation between expression and total length ( L T ) of fish was observed with the largest L T class (>125 mm) exhibiting significantly elevated pleurocidin expression as compared with fish in the smaller L T class. This indicates that immune competency may increase with age. No site‐specific differences in cyp1a expression were observed. These data suggest that exposure to aromatic hydrocarbon contaminants is fairly widespread throughout the study area and that any differences in pleurocidin expression in YOY P. americanus are probably due to other factors. Antimicrobial activity was also measured as a functional indicator of immune response. Activity was highly variable, showing no significant site‐specific differences, and no significant correlation to pleurocidin expression. The lack of correlation between pleurocidin expression and antimicrobial activity indicates that other antimicrobial peptides may be active against the bacteria tested or that other factors are influencing antimicrobial activity. This is the first quantitative evaluation of pleurocidin expression in YOY P. americanus from an urban area. Further work is needed to characterize factors controlling pleurocidin expression, as well as other indicators of immune response in young fish.

Combinatorial effects of administration of immunostimulatory compounds in feed and follow‐up administration of triple‐dose SLICE ® ( e mamectin benzoate) on A tlantic salmon, S almo salar L., infection with L epeophtheirus salmonis - J Poley; S L Purcell; O O Igboeli; A Donkin; H Wotton; M D Fast (Journal of Fish Diseases, 2013)
Several immunostimulatory feed additives have shown the ability to induce protective responses in A tlantic salmon to infection with L epeophtheirus salmonis . However, even the most encouraging results rarely surpass a 50% protective index in the host. That fact coupled with the well‐documented limitations of single‐therapy strategies in the effective management of parasitic infections generally make it imperative to identify therapies that can be combined in an integrated pest management approach for sea lice. With this in mind, we hypothesized that immunostimulatory feeds could enhance the protection provided by SLICE ® emamectin benzoate ( EMB ). To test this hypothesis, Atlantic salmon were fed one of two different immunostimulatory feeds ( CpG ODN or A quate ® ) for c . 7 weeks, challenged with L . salmonis copepodids early within that immunostimulatory feed period and then placed on a triple‐dose (150 μg kg −1 ) feed of SLICE ® for 1 week following the completion of the immunostimulatory feeding period. CpG ODN (2 mg kg −1 ) and the commercial yeast extract ( A quate ® 0.2%) inclusion in feeds were able to successfully induce inflammatory gene expression (interleukin‐1β) in the head kidneys of infected fish at 13 and 26 days post‐exposure ( DPE ), and 13 DPE , respectively. Lice burdens were lower on fish fed CpG ODN (18%) or A quate ® (19%) diets; however, due to variability, these were not statistically significant over time. Despite no statistically significant reductions in lice numbers, by 33 DPE fish on immunostimulatory feeds had significantly reduced cortisol levels when compared to infected fish on control diet. Cortisol levels in fish receiving an immunostimulatory diet were no different from initial baseline levels prior to infection, whereas the levels in control diet fish were significantly elevated from all other time points. Despite the positive effects on infection of fish fed immunostimulatory feeds, no synergism was observed with follow‐up treatment with SLICE ® . In fact, highest survival of lice was observed in fish with prior immunostimulation.

Immunostimulation of S almo salar L., and its effect on L epeophtheirus salmonis (Krøyer) P ‐glycoprotein mRNA expression following subsequent emamectin benzoate exposure - O O Igboeli; S L Purcell; H Wotton; J Poley; J F Burka; M D Fast (Journal of Fish Diseases, 2013)
Control of sea lice, L epeophtheirus salmonis , on farmed A tlantic salmon, S almo salar , relies heavily on chemotherapeutants. However, reduced efficacy of many treatments and need for integrated sea lice management plans require innovative strategies. Resistance to emamectin benzoate (EMB), a major sea lice parasiticide, has been linked with P‐glycoprotein (P‐gp) expression. We hypothesized that host immunostimulation would complement EMB treatment outcome. Lepeophtheirus salmonis ‐infected Atlantic salmon were fed immunostimulatory or control feeds. Sea lice were collected for 24‐h EMB bioassays 1 and 2 weeks prior to commencement of EMB treatment of the fish. Two weeks after cessation of immunostimulant‐treated feed, EMB was administered at 150 μg kg −1 fish biomass for 7 days. The bioassay revealed stage, gender and immunostimulant‐related differences in EMB EC 50 . Sea lice attached to salmon with a history of immunostimulation exhibited significantly greater survival than those on control feeds, despite similar levels of EMB in host tissues. Lepeophtheirus salmonis from salmon with a history of immunostimulation also exhibited higher P‐gp mRNA expression as well as greater survivability compared to controls. Administration of immunostimulants prior to EMB treatment caused increased expression of P‐gp mRNA which could have consequently caused decreased efficacy of the parasiticide.

Cp G inclusion in feed reduces sea lice, L epeophtheirus salmonis , numbers following re‐infection - S L Purcell; S E Friend; J M Covello; A Donkin; D B Groman; J Poley; M D Fast (Journal of Fish Diseases, 2013)
Lepeophtheirus salmonis infections in Atlantic salmon, S almo salar , have been characterized by little to no hyperplastic response and a biphasic immune response that results in chronic inflammation with tissue repair as the infection progresses. We hypothesized that C p G administration with prior lice exposure would enhance epithelial inflammatory mechanisms and boost the A tlantic salmon immune response to L . salmonis , leading to greater protection against infection. We administered multiple exposures of L . salmonis to two groups of A tlantic salmon and compared responses against first‐time exposed A tlantic salmon. Following re‐exposure, C p G fed fish exhibited increased skin expression of interleukin ( IL )‐1β and IL ‐12 β compared to control previously exposed ( CPE ) and control first‐time exposed ( CFE ) animals, respectively. This inflammatory enhancement occurred with significantly lower expression of matrix metalloproteinase‐9 ( MMP 9), both systemically (spleen) and locally (skin). Reduced MMP 9 expression was a hallmark of the re‐infected fish (occurred in both tissues at both times). When significant differences were present in the skin or spleen, the two re‐exposed groups showed greater similarity than with the first exposure group. Lice numbers on C p G fed fish were significantly lower than CFE fish at 7 days post‐re‐infection (dpri), and although they were not significantly different at 17 dpri, the trend of lower lice levels remained. CpG fed fish also showed nearly twofold greater protection than CPE when compared to the CFE group (48.5% vs. 27.0% reductions at 7 dpri and 27.2% vs. 13.1% reductions at 17 dpri, respectively). The enhanced protection of C p G oligodeoxynucleotide administration to previous exposure was consistent across all body surfaces and suggests that C p G can not only enhance innate responses to L . salmonis in A tlantic salmon, but also further stimulate adaptive responses.

Immunophysiology of Atlantic sturgeon, Acipenser oxyrinchus oxyrinchus (Mitchill), and the relationship to parasitic copepod, Dichelesthium oblongum (Abilgaard) infection - M S Sokolowski; B A Allam; K J Dunton; M A Clark; E B Kurtz; M D Fast (Journal of Fish Diseases, 2012)
The copepod parasite, Dichelesthium oblongum , is known to infect the Atlantic sturgeon, Acipenser oxyrinchus oxyrinchus , within the area near New York city, USA, known as the NY Bight. The gross pathology associated with the juvenile and adult copepod stages along with the parasite’s link in causing changes in sturgeon osmoregulatory capabilities has led us to investigate the host immunophysiology in relation to this host–parasite system. All the host variables, which included gill Na + ‐K + ‐ATPase activity, serum alkaline phosphatase (AP) and white blood cell differential counts, were affected in a non‐linear manner by the copepod parasite. The parasites increased the host gill Na + ‐K + ‐ATPase activity and serum AP along with the percentage granulocytes while decreasing the percentage lymphocytes. A new method, developed to sample and preserve white blood cells in the field for future flow cytometry analysis, proved adequate. The effects of fish size, location and time of sampling were accounted for by the use of generalized linear models, and their effects on the host variables are discussed.

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

The performance of RAMS in representing the convective boundary layer structure in a very steep valley - Stephan F. J. De Wekker; D. G. Steyn; J. D. Fast; M. W. Rotach; S. Zhong (Environmental Fluid Mechanics, 2005)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)